PEMBUATAN DAN PEMANFAATAN ANTISEPTIK DAN DESINFEKTAN DALAM PENCEGAHAN COVID-19 - Parawansah Parawansah; Saida Saida; Amiruddin Eso; Nurul Afifah Yusran; Wa Ode Chesaria F.A; Indriyati Indriyati; Nuzul Aulia Fajarwati B; Puteri Febriyanthi Rachman (Jurnal Pengabdian NUSANTARA, 2021)
Antiseptic is a chemical substance whose mechanism of action is to destroy microorganisms or inhibit its work so that it can prevent infection. One of the antiseptics is chlorhexidine and alcohol. The method used in this service is the comparative method of several journal sources. A literature study is conducted online by searching for journals. The results of this dedication show that the use of antiseptics and disinfectants to prevent Covid-19 transmission is effective if the selection is right and used according to their purpose. There needs to be further education by health workers to the public to be a preventive measure against the further spread of Covid-19.